Insights into abusive workplace behavior - Tziner, Aharon; Bar-Mor, Hadara; Shwartz-Asher, Daphna; Shkoler, Or; Geva, Lilach; Levi, Haim (Frontiers in Psychology, 2023)
This paper explores definitions, incidences, and outcomes of workplace abuse -a widespread, worldwide social phenomenon impinging on the well-being of workers in a developing labor market (Dumitru, 2016)and possible directions for delineating and standardizing classifications of the phenomenon that facilitate workers' protection.Furthermore, we employ Tepper's Abusive Supervision Survey Questionnaire [ASSQ] to identify managerial abuse in organizations regarding the type of organization (public/private), gender of the perpetrator, gender of the target, and the managerial role, of each of the abuse items. Finally, we suggest directions for further research and practical measures designed to facilitate the diminution of behavioral abuse in the workplace in the foreseeable future.No hypotheses are submitted in this exploratory paper.Employees of two large organizations (the Katzrin Local Council and Tigbur Ltd.) and another small national organization in Israel were approached, requesting their assistance in this investigation. We introduced the questionnaire, noting its anonymity and the academic context, and that subject participation was voluntary. The questionnaire consisted of fifteen statements on a five-point response scale ranging from 1 = "I cannot remember him/her ever using this behavior with me" to 5 = "He/she uses this behavior very often with me" (alpha = .97, M = 1.81, SD = 1.03).One hundred five respondents comprised the final sample: men (39%) and women (61%) aged 23-66. 66.7% of the respondents were employed in a public organization, 28.5% in a private organization, and 4.8% in a national organization. Years of education: Less than 12 (14.3%); 12 full years (17.1%); tertiary education (10.5%); bachelor's degree (40%); and master's degree and above (18.1%). While 28.6% held managerial positions, 71.4% did not.Job tenure ranged between 0.5 and 42 years. The participants in national and private organizations were combined to avoid the problem of unbalanced groups. Notably, the gender balance of the managers was men (50.5%) and women (49.5%).